2007
DOI: 10.1002/macp.200790002
|View full text |Cite
|
Sign up to set email alerts
|

Cover Picture: Macromol. Chem. Phys. 2/2007

Abstract: Cover: Schematic representation of an amphiphilic multi‐arm star‐block copolymer based on a hyperbranched polymer core. The copolymer was shown to be able to encapsulate and disperse significant loadings of volatile hydrophobic fragrances in aqueous media. Further details can be found in the Full Paper by C. Ternat, G. Kreutzer, C. J. G. Plummer, T. Q. Nguyen, A. Herrmann, L. Ouali, H. Sommer, W. Fieber, M. I. Velazco, H.‐A. Klok, and J.‐A. E. Månson* on page 131.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 0 publications
3
40
0
Order By: Relevance
“…Different types of unimolecular micelles based on multi-arm SABCs recently have been reported as hydrophobic drug delivery carriers [12][13][14][15]. Wang et al reported multi-arm SABCs with a large number of arms by ring-opening polymerization (ROP) of -caprolactone and l-lactide using polyamidoamide (PAMAM) as the macroinitiator followed by coupling with poly(ethylene glycol) (PEG) [12,13].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Different types of unimolecular micelles based on multi-arm SABCs recently have been reported as hydrophobic drug delivery carriers [12][13][14][15]. Wang et al reported multi-arm SABCs with a large number of arms by ring-opening polymerization (ROP) of -caprolactone and l-lactide using polyamidoamide (PAMAM) as the macroinitiator followed by coupling with poly(ethylene glycol) (PEG) [12,13].…”
Section: Introductionmentioning
confidence: 98%
“…Amphiphilic multi-arm SABCs have been prepared using a H40 macroinitiator by ROP of -caprolactone, followed by ATRP of tertbutyl acrylate for the encapsulation of fragrance molecules [15]. Chen et al reported folate functionalized nanoparticles based on H40, poly(-caprolactone) (PCL) and PEG; however, less attention has been given to the possible cross-linking between the neighboring molecules due to bifunctional PEG used as hydrophilic segments [16].…”
Section: Introductionmentioning
confidence: 99%
“…So far, several amphiphilic hyperbranched block copolymers have been prepared using H40 as the macroinitiator by ring‐opening polymerization (ROP), or atom‐transfer radical polymerization (ATRP), or reversible addition‐fragmentation transfer (RAFT) polymerization. The synthesis of amphiphilic hyperbranched block copolymer based on a hyperbranched H40 core, a hydrophobic poly( ε ‐caprolactone) inner shell, and a hydrophilic poly(acrylic acid) outer shell has been described for the improved micelle stability and drug loading ability 13. Recently, different types of thermo‐sensitive unimolecular micelles were prepared by RAFT polymerization of N ‐isopropylacrylamide and 2‐(dimethylamino)ethyl methacrylate using H40 as the macroinitiator 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…In dilute aqueous solution, the multi‐arm amphiphilic star block copolymers acted as unimolecular containers that could be loaded with up to 27 wt% hydrophobic guest molecules. In another study, the synthesis of amphiphilic multi‐arm star block copolymers with a H40 core, a hydrophobic PCL inner shell and a hydrophilic poly(acrylic acid) outer shell was described for the effective encapsulation and dispersion of fragrance molecules 39…”
Section: Modifications Of Hbpesmentioning
confidence: 99%